Interview: Back pain research. (November 2013) - Manniche, Claus
Professor Claus Manniche speaks to Adam Born, Assistant Commissioning Editor: Professor Claus Manniche graduated from the University of Copenhagen (Denmark) in 1982 with a degree in medicine and gained his license to practice in 1985. After gaining a law degree from the same university in 1988, Professor Manniche concentrated on the field of back pain and rheumatology, becoming a specialist Doctor in the latter area in 1994. He rejoined the University of Copenhagen as part of its medical faculty in 1995 before being appointed as Professor and Director of the Spine Center of Southern Denmark 3 years later, where he has since risen to the role of consultant. He has been a part of several influential committees and research groups including the Danish Rheumatology Society, the Copenhagen Back Research Association and, more recently, was appointed by the Minister of Health as a member of a specialist committee investigating the prevention of back problems. Professor Manniche has been a recipient of the Danish Society for Manual Medicine Honorary Award, 1989: Hvirvelsøjleprisen; a recipient of the Danish Chiropractors' Association Researcher Prize, 1991; and a recipient of the Scandinavian Journal of Rheumatology 's 40th Nordic Anniversary Prize in 1995. Two clinics that Professor Manniche helped to develop have also been recognized: the outpatient back clinic at Aarhus County Hospital (Denmark) received the 'Quality Award for the year 1996, Aarhus Amt'; the Back Center at Fyn was a recipient of the Danish Chiropractors' Association honorary award in 2008.